Putting the Evidence into Preceptor Preparation - Florence Myrick; Florence Luhanga; Diane Billay; Vicki Foley; Olive Yonge (Nursing Research and Practice)
The term evidence-based practice refers to the utilization of knowledge derived from research. Nursing practice, however, is not limited to clinical practice but also encompasses nursing education. It is, therefore, equally important that teaching preparation is derived from evidence also. The purpose of this study was to examine whether an evidence-based approach to preceptor preparation influenced preceptors in a assuming that role. A qualitative method using semistructured interviews was used to collect data. A total of 29 preceptors were interviewed. Constant comparative analysis facilitated examination of the data. Findings indicate that preceptors were afforded an opportunity to participate in a preparatory process that was engaging, enriching, and critically reflective/reflexive. This study has generated empirical evidence that can (a) contribute substantively to effective preceptor preparation, (b) promote best teaching practices in the clinical setting, and (c) enhance the preceptorship experience for nursing students.